Penerapan Tanggung Jawab Sosial Perusahaan Corporate Social Responsibility (CSR) Di Bidang Perkebunan Kelapa Sawit PT. Tri Bakti Sarimas Dalam Rangka Meningkatkan Kesejahteraan Masyarakat Kabupaten Kuantan Singingi Provinsi Riau - Maychel, Raja; ', Firdaus; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
CSR (Corporate Social Responsibility) is one of the obligations that must be implemented by the company in accordance with the contents of Article 74 of Law Company Limited (Company Law) to date, namely Law No. 40 In 2007, through this Act, companies are required to implement them. Increasing the level of awareness of quality of life, social harmonization and environment also affect the activity of the business world, it gives birth to a lawsuit against the company's role in order to have a social responsibility. Here is one of the benefits to be gained and the company's CSR activities. In this context the activities of Corporate Social Responsibility (CSR) became mandatory for the company menu, beyond the obligations outlined the Act.CSR activities in the beginning is a program that is voluntary or not must be implemented by the company. This understanding was changed when the government began to realize that CSR is very important to be implemented in particular on companies engaged in the plantation. This is because the plantation companies do not pay attention to the environment and the people who are around the plantation areas so that the environment becomes damaged and the welfare of the people do not change significantly as mandated by the constitution.This study aims to determine the application of corporate social responsibility / CSR PT. Tri Bakti Sarimas in order to improve the welfare of society Kuansing, Riau Province is in conformity with the expectations of society and to know the efforts made by PT. Tri Bakti Sarimas in order to improve public welfare Kuansing District, Riau Province.This research is a field research by collecting data obtained through interviews with the company and the community as well as attention to supporting literature. The data obtained and analyzed qualitatively and presented descriptively.The results showed that the application of CSR PT. Tri Bakti Sarimas still not in accordance with the nature and ideals of CSR desired by the Law for the implementation of CSR so far only to fulfill the obligations required by the Act. PT. Tri Bakti Sarimas also not meet the principles of decency and fairness because they CSR programs that they run just.giving money and greening the environment. CSR activities is the ideal community development activities so that people can become independent and prosperous society which is a long-term investment for the sustainability of the company. Keywords: CSR- Community - Environment